Academic Problems Among Iraqi University Professors: An Analytical Study - Jassim, Khalid Jamal; Kanbar, Huda Abbas; Ibrahim, Manal Mohammad; Al-Taai , Suaad Hadi Hassan (Journal of Ecohumanism, 2024)
The research aims to detect the problems of educational reality faced by university professors and identify statistically significant differences in the academic problems of university instructors. It has adopted an analytical descriptive research approach to achieve research objectives and identifies the study community with professors of public and private universities. A random sample of 250 instructors was selected for the purpose of applying the questionnaire to them, knowing the academic problems encountered in the course of their work at universities, and adopting appropriate statistical means to process and analyze the data. The research concluded with a set of results, including that all fields (infrastructure, admission of students, financial benefits, scientific research, university teaching, curriculum, equipment, and laboratories) are considered important academic problems, as the computational circles ranged from 2,775 to 2,562 degrees and the standard deviation ranged from 0.600 to 0.419 degrees.